Impact of losses in the resonance circuits on the F class amplifier operation - Крыжановский, В.Г.; Ефимович, А.П. (Radiotekhnika, 2012)
Output power and efficiency of F class amplifier was simulated and experimentally tested for various values of resistance in the resonance circuits. An amplifier on MOS transistor 2N7000 with operation frequency 13.56 MHz and output power 1.5 W was calculated, efficiency of 76 % was obtained. It was shown that the detrimental effect of losses on the amplifier’s efficiency can be reduced by tuning the circuits’ resonant frequencies depending on their quality factor. This phenomenon is explained by correction of phase shift between fundamental frequency’s current and voltage as the resonant frequencies of the output network circuits are tuned.